Daily life impact of malocclusion in Swedish adolescents: A grounded theory study. (May 2013) - Taghavi Bayat, Jari; Hallberg, Ulrika; Lindblad, Frank; Huggare, Jan; Mohlin, Bengt
Abstract Objective. To explore how malocclusions affect daily life in adolescents and how adolescents cope with malocclusion-related distress. Materials and methods. Twelve strategically selected teenagers, seven girls and five boys aged 13–14 years, participated in this study. Open, tape-recorded in-depth interviews based on Focus Group Discussions (FGD) were performed using a theme guide and analyzed according to the qualitative method of classic grounded theory (GT). Results. A core category was identified and named 'Repeatedly reminded of the malocclusion'. Associated to the core category, five categories were generated and labeled 'Being directed by the media's ideal image', 'Monitoring others' teeth', 'Struggling with low self-esteem', 'Hiding one's teeth' and 'Striving for cure'. Low self-esteem appeared to be frequently reinforced through the concerns for the malocclusion and handled via different coping strategies, such as hiding the teeth and striving to receive orthodontic treatment. Such processes were further enforced through the influence of media. Low self-esteem could be associated to a visible malposition of teeth, according to the informants. Having to wait for orthodontic treatment was frustrating the adolescents. Conclusions. Adolescents with malocclusion are often reminded of their condition, which can lead to avoiding strategies to minimize the negative feelings associated with the teeth and low self-esteem. Clinicians may therefore need to be aware of potential irrational behaviors when interacting with adolescents with malocclusions. The findings also suggest that there might be a discrepancy of attitudes between professionals focusing on oral health aspects of malocclusions and the adolescents focusing on esthetic aspects.